Perception of Menstruation and Practices among Adolescents in Urban Field Practice Area, Bangalore: A Cross Sectional Study - Navya Sri Sreenivasa; Saraswathi Sakranaik; Ranganath T Sobagiah; Viswanath (Medsci Publications, 2017)
Context: World health organisation has defined Adolescence as the period between 10-19 years of life. Good hygienic practices such as the use of sanitary napkins and adequate washing of the genital area are essential during menstruation. Assessing the hygienic practices among adolescents can be used as a baseline tool for formulating health education strategies. The Objectives of this study was to assess the knowledge, Attitude and Practices regarding Menstruation among the adolescent school girls. Methods and Material: A Cross Sectional Study was conducted among 400 adolescent girls by probability proportionate sampling. Data was collected by using a pretested, semi-structured questionnaire. Results are presented in terms of frequency and percentages. Results: Mean age of study participants was 14.16yrs + 0.9SD. Around 66.25% of students had heard about menstruation before attending menarche. Mothers were the main source of information. 80% of girls strongly believed that menstruation is a bothersome event. Majority used sanitary napkins as absorbent. Conclusion: The study revealed that 33.75% of adolescents were not aware about menstruation prior to menarche. 7.75% females were not allowed to go to school during menstruation. Thus the present study perceives the need to dispel misconceptions regarding menstruation to improvise and promote good menstrual hygiene practices.